2011
DOI: 10.5402/2011/962932
|View full text |Cite
|
Sign up to set email alerts
|

Study of Catalytic Effect of Nanolayered Montmorillonite Organoclays in Epoxy Polymer

Abstract: This paper is about the study of catalytic effect of nanolayered montmorillonite-(MMT-) based organoclays (OCs) in epoxy polymer by directly monitoring their exothermic temperature versus time during curing. Untreated clays (UCs) of MMT were also filled in the epoxy polymer for comparative study. OCs and UCs were individually filled in epoxy polymer from 0 wt.% to 5 wt.%, and the curing characteristics were examined. The cure behavior of epoxy-OC composites changes as a function of OC concentration. Among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Phenolic composites with 5 wt% of SiC provided the highest tensile strength of 36.6 MPa and phenolic composites with 5 wt% of MMT provided the highest tensile strength of 35.01 MPa, compared to neat PF which offered the tensile strength of 18.56 MPa. This is due to the load can transfer efficiently from polymer matrix to reinforcing fillers [7,8] corresponding to Mohan [8] that studied on the preparation of montmorillonite-epoxy composites and he found that the addition of montmorillonite increased the tensile modulus, elongation and strength of epoxy polymer. However, when the SiC or MMT contents were more than 5 wt%, the tensile strength of the phenolic composites were constant.…”
Section: Resultsmentioning
confidence: 99%
“…Phenolic composites with 5 wt% of SiC provided the highest tensile strength of 36.6 MPa and phenolic composites with 5 wt% of MMT provided the highest tensile strength of 35.01 MPa, compared to neat PF which offered the tensile strength of 18.56 MPa. This is due to the load can transfer efficiently from polymer matrix to reinforcing fillers [7,8] corresponding to Mohan [8] that studied on the preparation of montmorillonite-epoxy composites and he found that the addition of montmorillonite increased the tensile modulus, elongation and strength of epoxy polymer. However, when the SiC or MMT contents were more than 5 wt%, the tensile strength of the phenolic composites were constant.…”
Section: Resultsmentioning
confidence: 99%
“…Эффективными модификаторами поверхности ММТ являются катионные поверхностноактивные вещества, родственные иону NH 4 + . Чаще всего используют четвертичные аммониевые соли (ЧАС) [10]. Однако органомодифицированные слоистые силикаты начинают разлагаться при температуре выше 200 °С, следовательно, структура ПАВ постепенно разрушается даже до пиролиза [11].…”
unclassified